2019
DOI: 10.1007/s40200-019-00423-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alpha-lipoic acid supplementation on fasting glucose and lipid profiles among patients with stroke: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background and objective Stroke is a devastating condition with long-term comorbidities including metabolic abnormalities. Alpha lipoic acid (ALA), with its antioxidant properties, might improve metabolic status of patients, though current evidence is still inclusive. This systematic review of randomized controlled trials (RCTs) was conducted to summarize the existing evidence regarding the effects of ALA supplementation on fasting glucose and lipid profiles among patients with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…In line with our result, one study concluded that, ALA improved peripheral insulin sensitivity in type 2 diabetes mellitus [9]. One meta-analysis showed a significant lower levels of serum glucose after ALA supplementation in patients with stroke [24]. The beneficial role of alpha lipoic acid in lowering the fasting plasma glucose may be connected to its effect in modulating adenosine monophosphate-activated protein kinase (AMPK) [25] in skeletal muscle and beta-cells [26]& [27], which subsequently potentiates the insulin-secretory response of β cells to glucose [28].…”
Section: Discussionsupporting
confidence: 90%
“…In line with our result, one study concluded that, ALA improved peripheral insulin sensitivity in type 2 diabetes mellitus [9]. One meta-analysis showed a significant lower levels of serum glucose after ALA supplementation in patients with stroke [24]. The beneficial role of alpha lipoic acid in lowering the fasting plasma glucose may be connected to its effect in modulating adenosine monophosphate-activated protein kinase (AMPK) [25] in skeletal muscle and beta-cells [26]& [27], which subsequently potentiates the insulin-secretory response of β cells to glucose [28].…”
Section: Discussionsupporting
confidence: 90%
“…In line with our findings, Rahimlou and colleagues also reported a significant decrease in HbA1c, CRP, and FPG after ALA supplementation in their study ( 52 ). Moreover, other studies found that ALA supplementation had beneficial effects on CRP levels ( 13 , 14 ) and FPG ( 53 ). We did not observe any effect of ALA supplementation on lipid profile, including TC, LDL cholesterol, and HDL cholesterol concentrations, which was in line with observations of previous studies ( 16 , 53 ).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, other studies found that ALA supplementation had beneficial effects on CRP levels ( 13 , 14 ) and FPG ( 53 ). We did not observe any effect of ALA supplementation on lipid profile, including TC, LDL cholesterol, and HDL cholesterol concentrations, which was in line with observations of previous studies ( 16 , 53 ). In contrast, serum TC and LDL cholesterol levels significantly decreased following ALA supplementation ( 11 , 54 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings are particularly important because they encourage ALA use in a number of conditions in which ALA is actually proven to be effective. As a matter of fact, even though ALA supplementation has already been demonstrated to influence a broad spectrum of metabolic pathways including inflammation and glucose homeostasis [ 94 , 95 , 96 ], to the best of our knowledge this is the first time that ALA safety profile has been comprehensively evaluated through a pooled analysis of randomized placebo-controlled clinical studies.…”
Section: Discussionmentioning
confidence: 99%